2010
DOI: 10.1007/s11606-009-1238-8
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Prescribing Improves Medication Safety in Community-Based Office Practices

Abstract: ClinicalTrials.gov, Taconic Health Information Network and Community (THINC), NCT00225563, http://clinicaltrials.gov/ct2/show/NCT00225563?term=Kaushal&rank=6 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
137
1
9

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 172 publications
(155 citation statements)
references
References 19 publications
6
137
1
9
Order By: Relevance
“…Also in our study, overall error rates for nonabbreviation errors were no different at one year and baseline, despite the fact that the old system had very limited CDS, although due to our small sample size, we may not have been able to detect a significant difference. This is despite a low overall prescribing error rates for non-abbreviation errors compared to rates in other published studies using identical methodology 7,13 .…”
Section: Discussioncontrasting
confidence: 63%
See 3 more Smart Citations
“…Also in our study, overall error rates for nonabbreviation errors were no different at one year and baseline, despite the fact that the old system had very limited CDS, although due to our small sample size, we may not have been able to detect a significant difference. This is despite a low overall prescribing error rates for non-abbreviation errors compared to rates in other published studies using identical methodology 7,13 .…”
Section: Discussioncontrasting
confidence: 63%
“…As in other published studies, rule violations were not counted as errors 7,13 provider, extending data collection beyond two weeks if necessary.…”
Section: Data Collection and Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…2,3 A study of community-based office practices found that prescribing errors were reduced from 42.4 to 6.6 per 100 prescriptions at 1 year among adopters of e-prescribing, while there was no change among non-adopters (p < 0.001). 4 The inadvertent dispensing of discontinued medications is another form of medication error. Harvard Vanguard Medical Associates found that 1.5 % of electronically discontinued medications were still being dispensed at the pharmacy during a 12-month follow-up, and 34 % of these medications met criteria for higher risk of adverse events.…”
Section: Introductionmentioning
confidence: 99%